Distinctive optofluidic parallel waveguides - Chin, Lip Ket (2015)
Novel lightwave propagation and bending can be realized in optofluidics by designing the refractive index profile in the microchannel through diffusion via transformation optics. Diffusion in the microfluidic channel is controllable, tunable and reconfigurable, realizing sophisticated bidirectional gradient-index profile for light manipulation. In this paper, 3D optofluidic parallel waveguides are formed using Dean's flow in a microchannel with tunable nano-gap. Photon-tunneling is observed between the optofluidic waveguides, and due to the diffusion process, distinctive light propagation patterns are observed. In symmetrical waveguides, chirped coupling pattern is observed due to the relaxation in index contrast at the downstream. With the ease of changing the composition of the liquids, asymmetrical waveguides can be realized and complex leaky lightwave is observed. The demonstrated optofluidic parallel waveguides will open new doors for more sophisticated and elegant photonic elements such as Eaton lens, designing via transformation optics.